2021
DOI: 10.1007/s40615-021-01162-w
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Excess Mortality Between Indigenous and Non-Indigenous Brazilians in 2020: Measuring the Effects of the COVID-19 Pandemic

Abstract: This study aimed to estimate the number of excess deaths among Indigenous Peoples associated with the COVID-19 pandemic in 2020 and to assess the disparities in excess mortality between Indigenous and non-Indigenous Brazilians. A time series analysis of weekly mortality data including all deaths from January 2015 to December 2020 was conducted. The number of expected deaths for 2020 was estimated using an over-dispersed Poisson model that accounts for demographic changes, temporal trends, and seasonal effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The World Health Organisation could include oral health as a Core Health Indicator and the United Nations and World Bank could integrate oral health within their health surveillance programmes 61 . While universal dental care is a necessary step in bettering oral health outcomes and experiences for Indigenous communities, it is necessary to highlight that even for health conditions or areas of care where universal coverage is provided, disease and mortality rates remain disproportionate for Indigenous peoples 2,3,6,62 . Therefore, the importance of Indigenous leadership and IHW in oral health promotion and dental care provision cannot be understated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organisation could include oral health as a Core Health Indicator and the United Nations and World Bank could integrate oral health within their health surveillance programmes 61 . While universal dental care is a necessary step in bettering oral health outcomes and experiences for Indigenous communities, it is necessary to highlight that even for health conditions or areas of care where universal coverage is provided, disease and mortality rates remain disproportionate for Indigenous peoples 2,3,6,62 . Therefore, the importance of Indigenous leadership and IHW in oral health promotion and dental care provision cannot be understated.…”
Section: Discussionmentioning
confidence: 99%
“…61 While universal dental care is a necessary step in bettering oral health outcomes and experiences for Indigenous communities, it is necessary to highlight that even for health conditions or areas of care where universal coverage is provided, disease and mortality rates remain disproportionate for Indigenous peoples. 2,3,6,62 Therefore, the importance of Indigenous leadership and IHW in oral health promotion and dental care provision cannot be understated. A shift in funding provisions for oral health that supports Indigenous models of care, offers competitive salaries, and sufficient budgetary allotments for oral health education and resources in community-controlled health services is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Two national household surveys of seroprevalence of antibodies against SARS-CoV-2 in 133 cities showed an 87% higher adjusted prevalence among indigenous subjects compared to whites [10]. In addition, in the rst year of the pandemic, mortality among indigenous people was 16.7% higher than that observed in the general Brazilian population [12]. Age-speci c mortality rates [14] as well as hospital case fatality rates in all age groups, were also higher in indigenous subjects compared to other colour/race categories registered in Brazilian health information systems [13,14].…”
Section: Introductionmentioning
confidence: 90%
“…The Covid-19 pandemic has disproportionally impacted socially disadvantaged population groups in Brazil, including indigenous peoples [10][11][12][13]. In the rst trimester of the pandemic, there was a rapid increase in the risk of sustained transmission of Covid-19 in areas with an indigenous presence [11].…”
Section: Introductionmentioning
confidence: 99%
“…To reinforce the vulnerability of IP, another retrospective study identified that the excess of deaths in the general Brazilian population in 2020 showed an increase of 18.1% in relation to the expected value, while in IP this growth was substantially higher, at 34.8%. It is worth noting that this excess of deaths is directly related to the fatal cases of COVID-19[ 56 ]. This scenario can be even more serious as studies also raise the possibility of under-reported cases of COVID-19, leading to the belief that these rates may have been higher[ 57 , 58 ], and even leading to the possibility of risk of the decimation of the entire indigenous villages in the southern region of the country[ 59 ].…”
Section: Minority Groups During the Pandemicmentioning
confidence: 99%